Control strategy for a modified cascade multilevel inverter with dual DC source for enhanced drivetrain operation - Bendyk, Maciej; Luk, Patrick Chi-Kwong (IEEE, 2017)
This paper presents a new control strategy for a modified cascade multilevel inverter used in drivetrain operations. The proposed inverter is a three-phase bridge with its dc link fed by a dc source (battery), and each phase series-connected respectively to an H-bridge fed with a floating dc source (ultracapacitor). To exploit the potentials of the inverter for enhanced drivetrain performance, a sophisticated yet efficient modulation method is proposed to optimise energy transfer between the dc sources and with the load (induction motor) during typical operations, and to minimise switching losses and harmonics distortion. Detailed analysis of the proposed control method is presented, which is supported by experimental verifications.
Keywords: Multilevel inverter; dual energy source; switching strategy; drivetrain